EFFECTS OF ACTIVE REVIEW AND PANEL DISCUSSION ON STUDENTS' LEARNING OUTCOMES IN SENIOR SECONDARY ECONOMICS IN IBADAN, NIGERIA (2013)
Economics is offered by most students in the senior secondary schools in Nigeria. However, students' performance in the subject has been poor. This development has been attributed to several factors among which are teaching methodologies. Studies have shown that teacher centered techniques employed over the years had not improved students' performance. This trend necessitated the use of student centered techniques such as active review and panel discussion among others. Hence this study investigated the effect of active review and panel discussion techniques as well as the contributions of school location and verbal ability on students' achievement in and attitude towards Economics. The study adopted the pre-test, post-test control group, quasi-experimental design. Purposive sampling technique was used to select two Local Government Areas clustered on the basis of location (urban and rural). Simple random technique was used to select six schools and an intact class from each school. Three instruments were used: Achievement test in Economics (r = 0.84), Student Attitude to Economics Scale (r = 0.85) and Student Verbal Ability Test (r= 0.87). Active review, panel discussion and conventional instructional plans were used as teaching guides. Seven hypotheses were tested. Data were analysedusing descriptive statistics ( mean scores and standard deviation), Analysis of Covariance and Scheffe Post Hoc Multiple Comparison. There was a significant main effect of active review and panel discussion techniques on students' achievement in Economics (F(2,305)=86.61; p<0.05) and attitude to Economics (F(2,305)=252.64; p<0.05) Students in the panel discussion group scored highest (X ?= 29.08) followed by those in active review (X ?= 26.20) in achievement, panel discussion was also highest (X ?=51.22) followed by active review(X ?=38.47) in attitude to Economics. There was also a significant main effect of school location on achievement and attitude (F (1,305)=48.18; p<0.05) and (F (1,305)=19.70; p<0.05). Students in the urban schools had higher mean score X ?= 23.74; X ?=28.21) in Economics achievement than students from rural schools (X ?=19.09;X ?= 24.44) and also in attitude: urban(X ?=35.49; X ?=44.24) rural X ?= 27.88;X ? =40.38). However, there was no significant main effect of students' verbal ability on achievement, but it had significant main effect on attitude (F (2,305)=4.77; p<0.05).Active review and panel discussion together with school location had no significant interaction effect on achievement but there was a significant interaction effect of these teaching and learning techniques with school location on attitude to Economics(F (2,305)=14.551; p<0.05)and this was higher on students in rural schools than that of urban schools students whichimplies that students in rural schools achieved more through the treatment than students in urban schools.The use of active review and panel discussion learning techniques engendered students' achievement in and attitude towards Economics. Economics teachers should be encouraged to adopt these techniques in the teaching and learning processes irrespective of location of schools so as to improve students' attitude to Economics. Economics teacher's teaching methodologies should also be revised to include the use of variety of students' centered techniques.